P 88 Good outcome of resective epilepsy surgery in patients with non-lesional focal epilepsy after invasive evaluation with stereotactically implanted depth electrodes. Issue 10 (October 2017) - Vollmar, C.; Thorsteinsdottir, J.; Kreth, F.; Peraud, A.; Noachtar, S.
Abstract : Background: Resective surgery is an effective and safe treatment option for medically refractory focal epilepsy. Patients who require prior invasive EEG evaluation with intracranial electrodes are usually considered difficult candidates. The absence of an MRI-visible structural lesion and extratemporal seizure onset are also considered disadvantageous and some studies showed a lower seizure free outcome after surgery. Uncertainty in the identification of the epileptogenic zone, incomplete resection and smaller resection volumes have been discussed as possible explanations. Methods: All patients had noninvasive Video-EEG-monitoring and MRI scans, some had additional ictal SPECT, FDG-PET and/or DTI scans. Implantation of electrodes was planned individually, based on the conclusive interpretation of all available clinical and imaging data. After invasive Video-EEG-monitoring tailored resections were planned individually and were aided by an MRI-guided navigation system where labeled electrode localizations were available for reference. Clinical characteristics, details of electrode implantation, resection volume and postsurgical outcome were determined. Chi-square/ Fisher's exact test for categorical variables and Student's t -test/ Mann-Whitney U test for continuous variables were used for statistical analysis to identify prognostic factors for postsurgical outcome. Results: 70 patients were included (median age: 34.9 years). Structural MRI was non-lesional in 29 patients (41%) and showed a structural lesion in 41 (59%). 26 patients (37%) had temporal lobe seizure onset, 44 (63%) were extratemporal. Between 3 and 16 (median 9) depth electrodes were implanted. After a median follow up of 13.1 months 79% of the patients were free of all seizures (Engel IA). Another 17% were free or almost free of disabling seizures (Engel IB, IC and II). There was no significant difference between lesional (81% Engel IA) and non-lesional (77% Engel IA) patients ( p = 0.73), between temporal or extratemporal ( p = 0.81) and left- or right-sided ( p = 0.69) resection, nor between first resection and re-operation ( p = 0.78) or an effect of proximity to eloquent cortex ( p = 0.59). There was no difference in the average resection volume between lesional (28 cm 3 ) and non-lesional (26 cm 3 ) patients ( p = 0.64). Conclusion: Resective epilepsy surgery after invasive EEG with depth electrodes can achieve as good an outcome in non-lesional as in lesional focal epilepsy with temporal and extra-temporal seizure onset. The patient specific approach with individually planned implantation schemes allowed identification of the seizure onset in all patients. Re-operation after prior failed surgery and resections close to eloquent cortex also have good chances for successful seizure free outcome.